Embedded Pharmacists in Primary Care - MacKinnon III, PhD; Lamberton, PharmD (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
As healthcare delivery moves from a provider-centric approach to a more patient-centric approach, systems and payers need to reimagine how care and team-based care is delivered to patients and reimbursed. Thus, the goal should be to see the right patient, by the right provider, in the right place, for the right price, and where appropriate, with the use of the right pharmaceutical(s) - "5 P's". There continues to be a reduction in physicians that are pursuing primary care roles in the United States, thus exacerbating the ability to meet patient demand. Most patient encounters begin with or end with the prescribing of medication. Thus, a future where pharmacists are embedded in primary care settings allows these pharmacists to collaborate at the point-of-prescribing (i.e., in-clinic) and provides tremendous benefits to providers and patients. The pharmacist workforce is educated at the doctoral level, yet vastly underutilized and can assist in a collaborative approach in primary care. The collection of articles in the Special Issue "Embedded Pharmacists in Primary Care" highlight examples of models that have included pharmacists in the ambulatory setting providing services in chronic disease management, comprehensive medication management, and care of specific conditions such as diabetes.